Rosuvastatin-Loaded Glycerosomes as a Neuroprotective Strategy Against Hyperlipidemia-Induced Brain Dysfunction: Development, Optimization, and in vivo Evaluation - Mahran Mohamed Abd El-Emam; Mohamed Ibrahim; Milad Reda Qelliny; Mahmoud Mostafa; Marwa Mohamed El Sayed; Maha S. Kilany; Amira Ebrahim Alsemeh; Rania Said Moawad; Mohamed Fouad Mansour (Journal of Pharmaceutical Innovation, 2026)
Objective Brain injury and neurodegenerative conditions are largely caused by oxidative damage and endoplasmic reticulum (ER) stress spurred on by hyperlipidemia. To lessen these consequences in the brains of hyperlipidemic rats, this study assesses the therapeutic potential of both rosuvastatin glycerosomes (RSV GLSMs) and niacin. Methods The study had five groups: control, hyperlipidemia induced by poloxamer 407 (P407), RSV GLSMs, niacin, or a combination of RSV GLSMs and niacin. Serum samples were collected for lipid profile assessment, whereas brain tissues were harvested for Reverse Transcription Polymerase Chain Reaction, histopathological, and immunohistochemical analyses. Results The treatment of P407 significantly decreased high-density lipoprotein and increased serum triglycerides, although RSV GLSMs and niacin substantially mitigated these changes. Malondialdehyde also surged in P407 rats, and total antioxidant capacity was diminished. RSV GLSMs and niacin supplementation significantly improved antioxidative defenses, with the combination therapy exhibiting more pronounced effects. RSV GLSMs and niacin notably lessen ER stress–responsive gene expression, including Eukaryotic Initiation Factor 2 alpha (eIF2α), C/EBP Homologous Protein (CHOP), X-box Binding Protein 1 (XBP1), c-Jun N-terminal Kinase (JNK), Binding Immunoglobulin Protein (BIP), and Activating Transcription Factor 6 (ATF-6) levels. In addition, RSV GLSMs and niacin improved autophagy by downregulating the Mammalian Target of Rapamycin (mTOR) and p62, and upregulating Beclin1 and Microtubule-associated protein 1A/1B-light chain 3, type II (LC3-II). According to immunohistochemical findings, RSV GLSMs and niacin reduced reactive gliosis and modulated the expression of B-cell lymphoma 2/Bcl-2-associated X protein (Bcl-2/Bax). Histopathological findings exhibited improved brain morphology, reduced vacuolization, and normalized glial cell distribution in the RSV GLSMs and niacin combination group, closely resembling the control group. Conclusions Overall, RSV GLSMs and niacin effectively mitigate hyperlipidemia-induced brain damage by modulating oxidative stress, ER stress, and autophagy pathways, suggesting potential as a promising treatment strategy.